EFEKTIVITAS WEBSITE APLIKASI E-MAKARYO (AYOKERJO) SEBAGAI LAYANAN TATA KELOLA KETENAGAKERJAAN PROVINSI JAWA TENGAH - Alken Alda; Wijayanto Wijayanto (Journal of Politic and Government Studies, 2026)
e-Makaryo is a website-based employment governance application in Central Java that functions to address unemployment in the region. Based on preliminary observations, there is an extreme imbalance between the high number of job seekers and the limited availability of job vacancies, uneven distribution of employment opportunities, as well as poor user experience (UX) and technical system constraints. This study examines how effective this website application operates and identifies the factors influencing its performance. This research employs a descriptive qualitative method with data collected through in-depth interviews with both administrators and users of the e-Makaryo platform. The data were analyzed using the effectiveness theory proposed by John P. Campbell, which includes the indicators of program success, target accuracy, user satisfaction, input–output optimization, and comprehensive goal attainment. In addition, this study also applies the concept of web service in electronic government systems as a supporting analytical framework. The results show that the implementation of the e-Makaryo website application has not been fully effective in supporting employment services in Central Java Province. Several effectiveness indicators, such as program success and user satisfaction, demonstrate relatively positive outcomes through improved accessibility and efficiency in the job-search process. However, the indicators of target accuracy and input–output optimization remain suboptimal due to the mismatch between job seekers’ competencies and industry demands, as well as the low participation of companies within the system. Supporting analysis using website service quality indicators also reveals that aspects such as ease of use and relative advantage have performed relatively well, whereas compatibility with user needs and result demonstrability still require improvement. The effectiveness of the implementation is also influenced by several inhibiting factors, including limitations in managerial human resources, technical system constraints, and suboptimal coordination and participation from companies in utilizing the platform.